Critical role of the adhesion receptor DNAX accessory molecule-1 (DNAM-1) in the development of inflammation-driven dermal fibrosis in a mouse model of systemic sclerosis. Issue 6 (17th November 2012) - Avouac, Jérôme; Elhai, Muriel; Tomcik, Michal; Ruiz, Barbara; Friese, Manuel; Piedavent, Melanie; Colonna, Marco; Bernhardt, Gunter; Kahan, André; Chiocchia, Gilles; Distler, Jörg H W; Allanore, Yannick
Abstract : Objective: To investigate the contribution of the adhesion receptor DNAX accessory molecule-1 (DNAM-1) in the development of dermal fibrosis on gene inactivation and targeted molecular strategies. Methods: Human skin expression of DNAM-1 was determined by immunohistochemistry. Mice deficient for DNAM-1 (dnam1 −/− ) and wild-type controls (dnam1 +/+ ) were injected with bleomycin or NaCl. Infiltrating leucocytes, T cells, B cells and monocytes were quantified and inflammatory cytokines were measured in lesional skin of dnam1 −/− and dnam1 +/+ mice. The anti-fibrotic potential of a DNAM-1 neutralising monoclonal antibody (mAb) was evaluated in the mouse model of bleomycin-induced dermal fibrosis. Results: Overexpression of DNAM-1 was detected in the skin of patients with SSc (systemic sclerosis). Dnam1 −/− mice were protected from bleomycin-induced dermal fibrosis with reduction of dermal thickening (75±5%, p=0.03), hydroxyproline content (46±8%, p=0.04) and myofibroblast counts (39±5%, p=0.01). Moreover, the number of T cells was significantly decreased in lesional skin of dnam1 −/− mice (69±15%, p=0.0007). Dnam1 −/− mice also displayed decreased levels of TNF-α and IL-6 in lesional skin. Consistent with the gene inactivation strategy, treatment of mice with DNAM-1 neutralising mAb prevented dermal fibrosis induced by bleomycin with reduction of dermal thickness (64±6%, p=0.002), hydroxyproline content (61±8%, p=0.004) and myofibroblast counts (83±12%, p=0.002). Conclusions: An inactivation gene strategy showed that DNAM-1 exerts profibrotic effects by controlling T cell activation and cytokine release. A molecular targeted strategy confirmed that DNAM-1 neutralising mAb has potent antifibrotic properties, supporting the hypothesis that inhibition of DNAM-1 might be a promising new approach for the treatment of SSc and potentially other related fibrotic diseases.